THE ROLE OF MASS MEDIA IN SOCIALISATION AND WELL-BEING: THEORETICAL ANALYSIS AND PSYCHOSOCIAL ASPECTS - Harkusha Inesa; Dubinskyi Serhii (Alfred Nobel University Publisher, 2024)
The article undertakes a theoretical analysis of mass media as a means of mass communication, which is a vital factor in the socialisation and well-being of humanity. The article aims to conduct a theoretical analysis of the role of mass media as a crucial factor in socialisation and well-being, to identify its impact on the human psyche, mass consciousness, and behaviour. The article also aims to assess the level of media literacy in Ukraine, investigate both the positive and negative aspects of the influence of mass media on mental health and emphasise the importance of psychosocial support through mass media in crisis situations. The study uses theoretical methods (content analysis, comparative analysis, generalisation, and systematisation) as well as an analysis of empirical data on the level of media literacy in Ukrainian society. It has been found that communication in the internet space should be aimed at immersing individuals in the media environment and oriented towards self-realisation and consumption tools. It has been noted that mass media exert a certain influence on the human psyche, mass consciousness, behaviour, and thoughts, which affects the process of socialisation. The conducted analysis of scientific research showed that the media literacy level among people in Ukraine is increasing. In Ukraine's information space, electronic means of information transmission dominate. At the same time, it has been emphasised that information can control individuals, affect their psyche, and stimulate their thinking, actions, and deeds. It has been asserted that the process of information transmission is purposeful. It is determined that mass communication is not limited to specific videos or texts as tools of information transmission. It has been found that personal development is an uninterrupted process and continues even in complex and extreme conditions that exist in Ukraine now. It has been established that the crisis is a source of a person's development. It has been shown that mass media is a useful tool for psychosocial support. One of the most important approaches to psychosocial aid via mass media is the dissemination of helpful information and skills that can help people with various mental states, problems, etc. It has been emphasised that mass media can provide information about professional aid, the availability of useful resources to support mental health, and whatever. It has been found that mass media cannot replace professional psychotherapy or counselling, especially in severe cases. It has been highlighted that mass media can have both positive and negative effects on mental health, particularly causing stress, anxiety, and depression. It also has been noted that mass media have a greater impact on the psyche of teenagers than adults. It has been claimed that the positive impact of mass media includes their ability to effectively and diversely disseminate information, increase the level of users' education, provide new forms of entertainment and facilitate relaxation, as well as ease communication and establish new communicative connections. On the other hand, mass media can manipulate the psyche and public opinion, and spread fake news and disinformation, leading to a destructive impact on the psyche and developing dependence on them. It has been concluded that media have a significant influence on society, especially on children and youth, hence media literacy becomes essential for effective interaction with mass media and adequate behaviour in the information environment. In the modern world, where media play a crucial role in society and social issues, media literacy becomes an important competence for professionals in the field of psychosocial work. This professionally important quality encompasses understanding media systems, critical thinking, the ability to analyse social problems, readiness to communicate with media, and selfassertion in the media space.